ETR : Anamry Beauty Consultant Mary Kay / Norfarhana Samsul - Samsul, Norfarhana (2019)
The Mary Kay Cosmetics company was started by Mary Katherine Ash in 1963 and was designed to give women the opportunity to be apart of a business focused on motivation and recognition in an otherwise male-dominated business world. Currently, Mary Kay Cosmetics employs over 1.6 million consultants in 30 countries. ANAMRY BEAUTY CONSULTANT MARY KAY is one of the beauty consultant that need to share about benefit of Mary kay product. Before become a consultant is the user of product Mary Kay Because I have skin problem. After One year using Mary Kay product I joint to be a beauty consultant on 26 February 2019.